Personality Style and Its Relation With Level of Anxiety (International Journal of Nursing Education, 2022)
Background: Personality traits and anxiety disorders are dynamically interrelated. Personality refers to the long-established traits and patterns that propel individuals to consistently think, feel, and behave in certain ways. The aim of this study was to assess the Personality style and its relation with anxiety among young adults studying in selected Institutions of North India. Methods: A quantitative cross sectional study conducted among 211 young adults (18-24yrs) who were studying in selected Institutions of Northern India using convenience sampling technique. The data were collected by using Eysenck Personality Questionnaire to assess the type of personality and Beck Anxiety Inventory (BAI) to assess the level of anxiety. Results: The results revealed that among 211 young adults, 42.2% had Moderate Neuroticism personality, 59.2% had moderate Extraversion Personality, 49.8% of them had Mild Lie personality and 49.8% had Moderate Psychoticism Personality. 39.4% of them had Minimum Level of Anxiety and 37.4% had Mild level of Anxiety. Moreover, There was a significant correlation of anxiety with Neuroticism and lie as p<0.05 level of significance.